ELASTIC MAGNETIC FORM FACTORS FOR Li^7 - Dakhil, Zaheda (Iraqi Journal of Science, 2024)
Elastic magnetic electron scattering form factors have been calculated for the ground state J T-3/2 % of. Li in the framework of the many-particle shell model. The calculations are based on the model space wave functions of Cohen-Kurath interaction. The results are compared with the available experimental data. The data are reasonably explained up to q-3.0fim when the size parameter of the harmonic oscillator potential is reduced from that used to fit the root mean square charge radius.